Research on ecosystem services in Brazil: a systematic review - Parron,Lucilia Maria (2019)
Abstract Studies using the ‘ecosystem services’ (ES) approach developed in Brazil based on the framework of the Millennium Ecosystem Assessment (MEA), and range from quantitative and qualitative evaluation to the development of economic instruments for payment for ecosystem services (PES) or compensation for their maintenance, mainly for hydrological services. In order to summarize current knowledge regarding ES, the structure for teaching in ES, and also to provide a basis for future research in Brazil, we carried out a systematic review of publications on ES and a study on the availability of undergraduate and graduate courses related to ES. We found 282 publications for the 2006-2017 period, which included peer-reviewed articles, books, book chapters, theses, dissertations, articles in annals and technical publications. We identified current knowledge, knowledge gaps and trends in ES researches that may guide surveys and scenario analyses for future studies, in different biomes and regions of the country. Atlantic Forest and Amazon are the most-studied biome. Most of the studies were related to the evaluation of different types of ES and to the development of methodologies for their evaluation and monitoring. The most common ES are related to biodiversity, carbon sequestration and water.